Evaluation of Irish labour courts effectiveness - Krislov, J (Economic & Social Studies, 1972)
Government participation in the settlement of industrial disputes in Ireland is focused in the Labour Court. Created in 1946, the Court combines conciliation with an investigation and recommendation machinery. The former function is performed by the Conciliation Service, while the latter is performed by the Court's six members.
Keywords: Irish Labour Court; Effectiveness